A SIMPLE PARAFFIN EMBEDDED PROTOCOL FOR FISH EGG, EMBRYO, AND LARVAE - Gratiana Eka Wijayanti; Priadi Setyawan; Indah Dwi Kurniawati (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
This paper describes a simple protocol of paraffin-embedded histological section for fish eggs, embryo and larvae of the hard-lipped barb and the giant gourami. The specimens were fixed in Bouin solution, washed in 70% ethanol, then were dehydrated in a series of ethanol solution of increasing concentration until absolute ethanol was reached. The specimens were cleared in graded xylene and were infiltrated with liquid paraffin then were embedded in pure paraffin. Upon sectioning, at 4–5 µm thick the specimens were attached to the gelatin-coated glass slide and let to dry at room temperature or 37°C overnight. The specimens were deparaffinized in xylene, rehydrated then were stained with hematoxylin and eosin. After being dehydrated in graded ethanol, the specimens were cleared in xylene and were mounted with an organic mounting agent. Any step in preparing histological section including samples collection, fixation, dehydration, infiltration and embedding might contribute to the quality of histological features. A proper knowledge of the tissues beeing processed, fixative solution and the histological techniques is essential to gain good results. Bouin fixative is preferable to fix fish larvae and produce a good histological feature. Decalcification is necessary to produce a good histological section on the specimens containing bone.